2019
DOI: 10.1093/mnras/stz3500
|View full text |Cite
|
Sign up to set email alerts
|

Rest-frame UV properties of luminous strong gravitationally lensed Lyα emitters from the BELLS GALLERY Survey

Abstract: We present deep rest-frame UV spectroscopic observations using the Gran Telescopio Canarias of six gravitationally lensed Lyα emitters (LAEs) at 2.36 < z < 2.82 selected from the BELLS GALLERY survey. By taking the magnifications into account, we show that LAEs can be as luminous as L Lyα 30 × 10 42 erg s −1 and M UV −23 (AB) without invoking an AGN component, in contrast with previous findings. We measure Lyα rest-frame equivalent widths, EW 0 (Lyα), ranging from 16Å to 50Å and Lyα escape fractions, f esc (Ly… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 157 publications
(287 reference statements)
3
15
0
Order By: Relevance
“…BOSS-EUVLG1 is an extreme starburst galaxy with a starforming rate of 955 ± 118 M yr −1 , which can be considered an ultraluminous galaxy based on its UV luminosity (i.e., L 1500Å ∼ 10 12 L ). Its SFR is similar to those measured in high−z (Patrício et al 2016;Marques-Chaves et al 2020b). Red squares: Lyman break galaxies (Pettini et al 2000;Quider et al 2009Quider et al , 2010Dessauges-Zavadsky et al 2010;Marques-Chaves et al 2018).…”
Section: Ionized Outflows In Boss-euvlg1 Low-and Intermediate-z Star-...supporting
confidence: 66%
“…BOSS-EUVLG1 is an extreme starburst galaxy with a starforming rate of 955 ± 118 M yr −1 , which can be considered an ultraluminous galaxy based on its UV luminosity (i.e., L 1500Å ∼ 10 12 L ). Its SFR is similar to those measured in high−z (Patrício et al 2016;Marques-Chaves et al 2020b). Red squares: Lyman break galaxies (Pettini et al 2000;Quider et al 2009Quider et al , 2010Dessauges-Zavadsky et al 2010;Marques-Chaves et al 2018).…”
Section: Ionized Outflows In Boss-euvlg1 Low-and Intermediate-z Star-...supporting
confidence: 66%
“…Erb et al 2010;Jaskot & Oey 2014;Bosman et al 2019), they are empirically found to trace the systemic redshift in galaxies at z ≈ 2 − 3 (e.g. Shapley et al 2003;Erb et al 2010;Steidel et al 2016;Vanzella et al 2018;Marques-Chaves et al 2020). Wind models from Prochaska et al (2011) indicate that the detection of non-resonant emission suggest that there is little attenuation and that outflows only partially cover the source, particularly as we find that the spatial profiles of the non-resonant lines are similar to that of the UV continuum.…”
Section: Systemic Redshiftsupporting
confidence: 62%
“…The most striking property of BOSS-EUVLG1 is its brightness, and corresponding large luminosities at z 2.469, in both the rest-frame UV continuum (R 20.8) and nebular emission (fluxes in Lyα and Hα above 10 −15 erg s −1 cm −2 , Table 1). Such apparent fluxes are much larger than those observed in typical SFGs (factors ≈ 30; e.g., Reddy & Steidel 2009;Sobral et al 2018a) and are only comparable to those observed in highly magnified lensed systems (e.g., Shu et al 2016;Marques-Chaves et al 2020) or in QSOs (e.g., Pâris et al 2014).…”
Section: The Nature Of Boss-euvlg1mentioning
confidence: 60%
“…Instead, the large luminosities arise from a large number of OB stars present in the first stages of an intense burst of star-formation. We compare the wind line profiles of N v and C iv to those obtained with the spectral synthesis code Starburst99 (S99: Leitherer et al 1999) to infer the age and metallicity of the stellar population (details in Marques-Chaves et al 2018, 2020. P-Cygni profiles are well modeled by a Z/Z 1/5 and 4 Myr burst of star formation (Fig.…”
Section: Boss-euvlg1 As An Extremely Luminous Starburstmentioning
confidence: 99%